2016
DOI: 10.1371/journal.pone.0154090
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota Is Influenced by Gender and Body Mass Index

Abstract: Intestinal microbiota changes are associated with the development of obesity. However, studies in humans have generated conflicting results due to high inter-individual heterogeneity in terms of diet, age, and hormonal factors, and the largely unexplored influence of gender. In this work, we aimed to identify differential gut microbiota signatures associated with obesity, as a function of gender and changes in body mass index (BMI). Differences in the bacterial community structure were analyzed by 16S sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
389
8
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(463 citation statements)
references
References 55 publications
34
389
8
8
Order By: Relevance
“…In contrast, higher relative abundance of Escherichia [64] and Veillonella genera and lower relative abundance of the Bilophila genus have all been described in males [63]. However, another study showed increased Bacteroides in males compared to females [59].…”
Section: Sex Differences In the Git Microbiota—human Studiesmentioning
confidence: 99%
“…In contrast, higher relative abundance of Escherichia [64] and Veillonella genera and lower relative abundance of the Bilophila genus have all been described in males [63]. However, another study showed increased Bacteroides in males compared to females [59].…”
Section: Sex Differences In the Git Microbiota—human Studiesmentioning
confidence: 99%
“…Host-derived variables, like gender and genetics, are known to impact the microbiota. 102,103 The list is longer for environmental variables, inducing the diet (e.g. fibre content, antibiotics/probiotics), housing (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, se debe reconocer que el género puede afectar la composición de la microbiota, ya que diferencias entre hombres y mujeres han sido descritas 23,24 . Asimismo, algunos trabajos sugieren que el género puede tener una influencia en la microbiota intestinal en distintos patologías, tales como síndrome de intestino irritable y EII 25,26 .…”
Section: Discussionunclassified